Determining the factors affecting attitudes towards family planning among university students - Gür Boz, Arife; Uysal Toraman, Aynur (International Journal Of Community Medicine And Public Health, 2023)
Background: Within the scope of reproductive health, family planning services play a key role in gender equality and empowerment of women. It is considered a human right to have access to these services. The literature has no study aimed at determining the impact of sociodemographic characteristics and gender roles of young people on their family planning attitudes. In Turkiye where the impacts of the patriarchal structure continue to be seen, studies on family planning are only conducted with married people or women. Methods: The sample of the descriptive correlational study comprised 1288 students receiving education in undergraduate programs in a university in Turkiye. In collection of the study data, the researchers used the Student Identification Form, the Gender Roles Attitude Scale and the Family Planning Attitude Scale. In order to determine the independent factors affecting attitudes towards family planning among the students, the researchers created a linear regression model. Results: Examining the Beta coefficient of the regression model used, the gender, faculty and grade of the students and their gender roles scores affected their attitudes towards family planning in a positive direction (F=40.097, p<0.005). Ordering the degree of independent variables to affect the attitudes towards family planning in the regression model according to the Beta coefficient, the independent variable that most affected the attitudes towards family planning was gender roles attitude. Conclusions: The study revealed that the gender roles attitude affected the family planning attitude.